Association of severe early childhood caries with iron deficiency anemia - Kalpana Bansal; Meetu Goyal; Renuka Dhingra (Wolters Kluwer Medknow Publications, 2016)
Background: Severe tooth decay is known to affect the health and well-being of young children. However, there has been minimal research showing the association of severe early childhood caries (S-ECC) and iron deficiency anemia (IDA). Aims: The primary aim of this study was to investigate an association between S-ECC with IDA. The secondary objective was to find an association between severe caries and body weight of the child. The oral health-related quality of life of children with S-ECC was also assessed. Materials and Methods: Following the ethical approval, 60 children aged 2-6 years (30 with S-ECC and 30 controls with caries status <2) were recruited for this cross-sectional association study. Each child received a clinical examination for dental caries status using deft index and a blood investigation to determine various parameters; hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration, and packed cell volume (PCV). Children underwent venipuncture after due parental consent, and 2.5 mL blood was collected from each child to evaluate the above parameters. Following this, the parents filled up a 10 point questionnaire to determine the child's quality of life. Data were then analyzed by t-test and Fischer's exact t-test. Result: On comparison of percentage of children with IDA in S-ECC and control group, it was found that children with S-ECC were more likely to have IDA odds ratio (95% confidence interval): 10.77 (2.0, 104.9), (P = 0.001). In addition to this, S-ECC children were significantly more likely to have low Hb, MCV, and PCV levels (P < 0.001) which imply that S-ECC may be a risk marker for the development of anemia. More children (93%) with severe caries were found to have less body weight than ICMR standard weight for age as compared to children with low caries (P < 0.05%). Conclusion: S-ECC is strongly associated with the anemia due to iron deficiency, and efforts should be made toward the preventive and curative aspects of ECC, which may improve the general well-being and quality of life of a child.